Comparative Advantages and Specialization Dynamics in Agri-food Trade of Argentina, Paraguay and Uruguay - Zdráhal, Ivo; Hrabálek, Martin; Kadlec, Petr; Krpec, Oldřich (Faculty of Economics and Management, Czech University of Life Sciences Prague, 2025)
The article interrogates the shape, dynamic, and fragility of revealed comparative advantages of 46 agri-food products traded by Argentina, Paraguay, and Uruguay in the period 1995-2020 using normalized revealed comparative index and summary statistics, stochastic kernels, Galtonian regression, Markov chains, and Kaplan-Meier survival analysis. The analysis reveals the agri-food flagship products and the agri-food trade of these countries has formed mainly around these flagship products. The results support the argument that changes in distribution of comparative advantages in agri-food trade underwent an increase in specialization in these countries, especially in the period from the beginning of millennia until about period slightly after the Great Recession. The results also indicate slight convergence in the change in agri-food comparative advantages in these three countries, as well as the increased complexity of agri-food comparative advantages in Argentina and Paraguay at the end of the period under scrutiny. Despite these variations and differences among countries under scrutiny the distribution of comparative advantages remains stable and persistent. Given this evidence, we conclude that these countries will continue to develop their agriculture-led growth economic model and these flagship products will play an important role in the overall agri-food export structures of these countries in the future.
Keywords: Liberalization; Markov chain model; regression analysis; revealed comparative advantage; RCA; agri-food trade